PERBANDINGAN HASIL PRODUKSI PETANI KENTANG DI DESA PASIR JAYA DENGAN DI DESA LINDUNG JAYA KABUPATEN KERINCI - Junisma, Hesvia - (Pendidikan Geografi, 2014)
This study aims to get the data, process, analyze and discuss the comparison of potatofarmers in Pasir Jaya Village with farmers in Lindung Jaya Village potato growers. This type ofresearch is classified in Comparative Descriptive study. The study population was all potatogrowers and farmers Pasir Jaya Village with Lindung Jaya Village potatoes. Samples were takenby using Slovin formula that totaled 68 samples of potato growers, potato farmers 34 respondentsPasir Jaya Village and 34 potato farmer respondents Lindung Jaya Village. The data was collectedusing a questionnaire guided, statistical analysis used is descriptive by using the formulapercentages and hypothesis testing. The results showed as follows: 1) There are differences in theincome generated by the sale of potato farmers in Pasir Jaya Village with potato farmers LindungJaya Village, because the value -tarithmethic <ttable (-6.598 <- 1.996), where the potato farmerincome Lindung Jaya village more than income potato growers Pasir Jaya Village, 2) There aredifferences in the production of potato farmers in Pasir Jaya Village with potato farmers LindungJaya Village, because the value âtarithmethic <ttable (-2.838 <- 1.996), where the production ofpotato farmers Lindung Jaya Village more than the production of farmers responsiveness PasirJaya Village, 3) There are differences in the marketing of potato in farmers Pasir Jaya Village withpotato farmers Lindung Jaya Village, because -tarithmethic <ttable (-8.614 <- 2.000), where thepotato farmer marketing Lindung Jaya Village more than potato farmers marketing Pasir JayaVillage and 4) There are differences in the accessibility of the Pasir Jaya Village potato growersand potato growers Lindung Jaya Village, because -tarithmethic <tTable (-25.616 <- 2.000), whereaccessibility to Lindung Jaya Village potato farmers more viable than potato farmers accessibilityto the of Pasir Jaya Village.